2020
DOI: 10.1021/acsapm.0c00731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent Molecular Structure on Diffusion through Plasticized Poly(vinyl chloride) Films

Abstract: Diffusion of organic solvents in plasticized poly-(vinyl chloride) (PVC) films is industrially significant for inkjetprinted PVC graphic displays, but comprehensive research on the mechanism of solvent diffusion in such systems is lacking. This study employs two easy-to-implement experimental techniques for diffusion measurement and reports on both the steady-state and non-steady-state diffusivities of 20 industrially relevant organic solvents, spanning five chemical moieties, in a commercial PVC base film. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(95 reference statements)
1
6
0
Order By: Relevance
“…The slope (m) of these linear fittings, thickness (L) of the composite and equilibrium molar sorption (S α ) was substituted in Equation to obtain the solvent D. It is observed that for the unfilled and filled NR, the D and P decreases with the increase in molecular weight of the solvent, that is, D p‐Xylene < D toluene < D benzene . The diffusion and permeation of a solvent through a polymer also depends on the size and molecular weight of the solvent 36 . The lower the size or kinetic diameter and the lower the molecular weight of the solvent, the higher will be its D or P. The kinetic diameter of benzene, toluene and p‐xylene are 0.59 nm, 0.61 nm and 0.67 nm, repectively 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope (m) of these linear fittings, thickness (L) of the composite and equilibrium molar sorption (S α ) was substituted in Equation to obtain the solvent D. It is observed that for the unfilled and filled NR, the D and P decreases with the increase in molecular weight of the solvent, that is, D p‐Xylene < D toluene < D benzene . The diffusion and permeation of a solvent through a polymer also depends on the size and molecular weight of the solvent 36 . The lower the size or kinetic diameter and the lower the molecular weight of the solvent, the higher will be its D or P. The kinetic diameter of benzene, toluene and p‐xylene are 0.59 nm, 0.61 nm and 0.67 nm, repectively 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion and permeation of a solvent through a polymer also depends on the size and molecular weight of the solvent. 36 The lower the size or kinetic diameter and the lower the molecular weight of the solvent, the higher will be its D or P. The kinetic diameter of benzene, toluene and p-xylene are 0.59 nm, 0.61 nm and 0.67 nm, repectively. 37 Hence, the above trend of D or P may be attributed to the increasing molecular weight and kinetic diameter of the solvents in the order benzene<tolue-ne<p-xylene.…”
Section: Diffusion and Permeation Coefficientmentioning
confidence: 99%
“…Second, one long precursor exposure likely leads to greater penetration and doping depths in comparison to multiple short cycles. It is likely that an extended singular exposure likely permits for increased vapor transport and diffusion depths for all systems (vide infra) …”
Section: Resultsmentioning
confidence: 99%
“…It is likely that an extended singular exposure likely permits for increased vapor transport and diffusion depths for all systems (vide infra). 54 To further quantify the optical and electrical properties for the 400 min VPI hybrid films, three sets of additional measurements were performed (see Figure S6). First, after VPI doping, the hybrid films' electrical conductivities were measured as a function of ambient exposure time (Figure S6a).…”
Section: Iiiiii Optical and Electrical Properties Of Ticlmentioning
confidence: 99%
“…However, the ease of migration of the plasticizer into the environment with aging and treatment renders the vinyl gloves less flexible and reduces their physical properties [ 32 ]. In this study, the leaching stability of the plasticizers from vinyl as a result of the sterilization methods and cycles was studied by soaking the glove specimens in n-hexane, which is a good solvent for phthalates [ 33 ].…”
Section: Resultsmentioning
confidence: 99%